A history of the confinement of inebriets, alcoholics and vagrants during the First Republic: lessons for current policies? - Pontes, Alexandre Kerr; Leal Ferreira, Arthur Arruda; Bicalho, Pedro Paulo Gastalho (Revista de Psicología, 2019)
This work elaborates on current drug policies by returning to some moments of uncertainty in these practices, especially the rearrangements between concepts of inebriety, alcoholism and vagrancy in Rio de Janeiro at the turn of the 20th century. We analyse the process of confinement through the contravention of drunkenness in Brazil’s 1890 Penal Code. We understand that the confinement related to alcohol abuse between 1899 and 1920 was developed by means of specific objects and practices: the drunken vagrant and the insane alcoholic. These forms of knowledge and practices were studied from primary sources produced by psychiatric and law enforcement institutions, with the police as main actor of these processes. Since drugs can be approached both from a public safety or public health bias, it seems apparent that past conceptions and practices of confinement seem to uphold. Drug users currently navigate through taxonomies that ricochet from criminals to mentally ill (chemical dependents), varying according to the circumstances. As such, it is important to observe the ways by which we delineate our social categories and their correlated practices.